REASONS RELATED TO THE DETERIORATION OF POULTRY INDUSTRY FOR BROIERS IN THE MIDDLE AND SOUTHERN REGION OF IRAQ - AL- Ani, G. A.A.; AL- Badri, A. A.N. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The objective of this research is to identify the reasons related to deterioration of the poultry industry for broilers in the middle and southern regions of Iraq. In order to achieve the research goals a questionnaire form consists of two parts was designed, the first part included a quadrilateral scale of (54) items distributed in to eight base fields. The second part included a five scales with (20) items. The results showed that, the imported product field achieved the first position among the reasons that related to the deterioration of poultry industry for broilers, which achieved the highest weighted average by 2.8 degree and a weight percentage of 93.3%. While the direction field of the broilers breeders was ranked the last position among the reasons that related to deterioration in poultry industry for broilers, which achieved the lowest weighted average which is 2.6 degree with weight of 86.6%. The results also, showed that the item start working with the integrated production companies in the poultry industry to produce poultry meat was ranked in the first position among the proposed solutions from the broilers breeders’ points of view to face the deterioration of the poultry industry for broilers, which ranked the highest weighted average of 4.9 degrees and a percentage weight of 98%. Finally, the item Control the importer’s hatching eggs was ranked the last position among the proposed solutions from the broilers breeders’ points of view to face the deterioration in the poultry industry for broilers, which achieved the lowest weighted average by (4.5) degrees and a percentage weight of 90%.